Long-term latitudinal effects of precipitation change in global monsoon regions - Ye, Wangting; Li, Yu; Feng, Zhuowen; Zhang, Yuxin; Peng, Simin (Frontiers in Earth Science, 2022)
Global paleo-monsoon precipitation evolution is confined to asynchronous response with global monsoons to shared forcings, which includes summer insolation, sea surface temperature, coupling of atmospheric circulation, and ocean circulation. However, most studies are based on conclusions drawn from a single or a few discrete records or deduced from top-down climate models and limited our ability to understand the latitudinal effect of monsoon precipitation. In particular, precipitation is a local constrained climate factor. Here, we present a comprehensive assessment of global monsoon precipitation since the last 12,000 cal year BP, including modern observations, paleoclimate simulations, paleo-climate records, and monsoon precipitation reconstruction over the past 12,000 cal year BP based on a bottom-up algorithm called climate field reconstruction approaches. Results show that the middle latitude monsoon precipitation is in line with the evolution of the insolation, and there is no significant long-term decreasing (increasing) trend in low latitude monsoon precipitation during the last 12,000 years BP. For modern monsoon evolution, the monsoon precipitation is also changed along with the meridional direction, with overall decreasing precipitation in the global monsoon region and increasing precipitation in the monsoon margin area. Monsoon systems at different latitudes all record eight Holocene weak precipitation events including the Younger Dryas (12,900 cal year BP to 11,700 cal year BP), which can be considered as a strong effect of a significant reduction or collapse of a meridional ocean circulation system - the Atlantic Meridional Overturning Circulation. At the same time, the low and middle latitude monsoon precipitation lags about 2,000 years behind the onset of North Atlantic warming. Taken together, our findings provide important insight into the latitudinal effect of monsoon precipitation at different locations.